Prove that sin^4x=cos^4x+sin^2x-cos^2x?

Asked on by xav1394

1 Answer | Add Yours

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

Moving cos^4 x to the left side yields:

`sin^4 x - cos^4 x = sin^2 x- cos^2 x`

Using the formula of difference of squares to the left side yields:

`sin^4 x - cos^4 x = (sin^2 x- cos^2 x)(sin^2 x+ cos^2 x)`

Use the basic formula of trigonometry, `sin^2 x+ cos^2 x = 1` , such that:

`sin^4 x - cos^4 x = (sin^2 x- cos^2 x)*(1)`

`sin^4 x - cos^4 x = (sin^2 x- cos^2 x)`

The last line proves that the original identity is verified.

We’ve answered 320,051 questions. We can answer yours, too.

Ask a question